1977
DOI: 10.1136/hrt.39.10.1082
|View full text |Cite
|
Sign up to set email alerts
|

Aortic root and left atrial wall motion. An echocardiographic study.

Abstract: The echocardiographically recorded movement of the aortic root was studied by analysing the relation between posterior aortic wall motion and other intracardiac events. The systolic anterior movement of the aortic root continued beyond aortic valve closure and in cases with mitral regurgitation began significantly earlier than in normal subjects. The diastolic rapid posterior movement began after mitral valve opening but did not occur in patients with mitral stenosis. The total amplitude of aortic root motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Anterior‐posterior displacement of the aortic root has been described by M‐mode echocardiography and has recognized as the primary manifestation of dynamic left atrial volume changes, as the annular and lateral atrial walls have lesser effects and the posterior left atrial wall is fixed . Mean displacement is 0.9 cm in normal state, and is increased in states associated with higher left ventricular stroke volume . This is not dissimilar to the mean of 1.16 cm obtained in our control group of patients with normal ejection fraction, considering the possibility of anemia, inflammatory states, test anxiety or other mitigating stress in these patients.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Anterior‐posterior displacement of the aortic root has been described by M‐mode echocardiography and has recognized as the primary manifestation of dynamic left atrial volume changes, as the annular and lateral atrial walls have lesser effects and the posterior left atrial wall is fixed . Mean displacement is 0.9 cm in normal state, and is increased in states associated with higher left ventricular stroke volume . This is not dissimilar to the mean of 1.16 cm obtained in our control group of patients with normal ejection fraction, considering the possibility of anemia, inflammatory states, test anxiety or other mitigating stress in these patients.…”
Section: Discussionsupporting
confidence: 57%
“…Although the motion of the ascending aorta was depicted by M‐mode echocardiography decades ago, its etiology is still poorly understood. Some investigators have attributed the anterior aortic displacement in systole to left atrial filling, while others credit the motion to left ventricular ejection and stroke volume . Although not a standard measurement, mean anterior aortic excursion is easily obtainable and mea‐sures approximately 0.9 cm in normal state .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We prospectively performed echocardiography in patients who underwent left-sided cardiac catheterization because of recently diagnosed coronary artery disease or suspected coronary artery disease from January 2000 to June 2001 and who met the criterion of sinus rhythm. Exclusion criteria were: (1) atrial fibrillation rhythm; (2) severe mitral stenosis or regurgitation; (3) severe aortic valve disease; (4) prosthetic valves; (5) pacemaker implantation; (6) congenital heart disease; (7) systolic blood pressure ≥160 mmHg or diastolic blood pressure ≥90 mmHg; and (8) inadequate quality of echocardiographic image. All study subjects underwent echocardiography within 4 hours of cardiac catheterization.…”
Section: Patientsmentioning
confidence: 99%
“…He argued from purely anatomical evidence that during left ventricular systole the aortic root would move forwards as the left atrium filled. Recent echocardiographic studies (Strunk et al, 1976b(Strunk et al, , 1977Akgiin and Layton, 1977) have confirmed this prediction, that normal aortic root movement occurs mainly in response to left atrial volume changes, though the contributions of left ventricular ejection and elastic recoil of the aorta have yet to be defined (Pratt et al, 1976).…”
mentioning
confidence: 97%